Dirkursus Tafsir di Masa Para Sahabat dan Ruang Lingkupnya - Akmal Rizki Gunawan Hasibuan; Syaza El-Millah Mtd; Sabila Phutri Balqis (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This writing aims to explain the differences in interpretation of the Qur'an among friends. The research methodology uses a descriptive analysis method with a qualitative approach by applying the library research type of research. The results and discussion of this research show several pros and cons between the two interpretive views of marfu' and mauquf and the emergence of differences in interpretation among friends which are driven by two causes. First, the reason for dzatiyyah is a reason related to the personality of the commenter. For example, the level of knowledge, accuracy, ability to listen carefully or not tell stories, it could be wrong if you obey the law. The second is the reason for maudzu'iyyat, namely reasons related to the text or dilalah. Such as differences in the qiraat side, the irab side, controversies among linguists in the interpretation of sentences, the pronunciation of isytarak, am khas, muthlaq and muqayyad, haqiq and majazi, idlmar and istiqlal, sentence additions, the beginning and end of a series, muhkam and mansukh, differences in story interpretation.